Four weeks of intensified training decreases resting metabolic rate in elite rowers - Woods, A.; Garvican-Lewis, L.; Lundy, B.; Rice, A.; Thompson, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Elite rowers must complete a high volume of training across a number of exercise modalities to build aerobic endurance, anaerobic power, strength and technical ability. Periods of heavy training may influence energy expenditure and subsequently, resting metabolic rate (RMR). Appropriate periodization of training is important to ensure consistent preparation and adaptation to the work prescribed, and to minimize illness and injury risk. Methods: Seventeen national-level rowers undertook a four-week period of intensified training. A block periodization approach was employed, emphasizing endurance capacity. RMR, body composition (DXA) and rowing performance were assessed PRE and POST the four-week period. Wellness was evaluated weekly using the Multicomponent Training Distress Scale (MTDS). Key on-water and ergometer sessions were monitored for physiological parameters. Results: Significant decreases were observed in: (mean ± SD of difference, p-value): absolute RMR (-466 ± 488 kJ.day-1, p = 0.01) and relative RMR (-1.91 ± 1.95 cal.kg.FFM-1, p = 0.01) in the ten athletes who completed the training block. Significant reductions in body mass (-1.64 ± 1.28 kg, p = 0.003) and fat mass (-2.20 ± 1.22 kg, p = 0.0001) were also observed, while energy intake was unchanged. Rowing performance did not improve. Fatigue and total mood disturbance were significantly increased across the training period (Tests of Within-Subjects Effects: F(5, 45) = 5.413, p = 0.001; F(5, 45) = 3.180, p = 0.02), but post-hoc analysis did not determine the time point of change. Discussion: Four weeks of heavy training decreased RMR and body composition in elite rowers, likely due to an imbalance between training load and energy intake. Future training cycles of this nature should ensure energy needs are met to enhance physiological adaptation and performance.